Effect of plyometric training on vertical jump performance in female athletes: A systematic review and meta-analysis - Stojanovic, E.; Ristic, V.; McMaster, T. D.; Milanovic, Z. (Sports Medicine, 2017)
Plyometric training is an effective method to prevent knee injuries in female athletes; however, the effects of plyometric training on jump performance in female athletes is unclear. Objective: The aim of this systematic review and meta-analysis was to determine the effectiveness of plyometric training on vertical jump (VJ) performance of amateur, collegiate and elite female athletes. Methods: Six electronic databases were searched (PubMed, MEDLINE, ERIC, Google Scholar, SCIndex and ScienceDirect). The included studies were coded for the following criteria: training status, training modality and type of outcome measures. The methodological quality of each study was assessed using the physiotherapy evidence database (PEDro) scale. The effects of plyometric training on VJ performance were based on the following standardised pre-post testing effect size (ES) thresholds: trivial (<0.20), small (0.21-0.60), moderate (0.61-1.20), large (1.21-2.00), very large (2.01-4.00) and extremely large (>4.00). Results: A total of 16 studies met the inclusion criteria. The meta-analysis revealed that plyometric training had a most likely moderate effect on countermovement jump (CMJ) height performance (ES = 1.09; 95 % confidence interval [CI] 0.57-1.61; I2 = 75.60 %). Plyometric training interventions of less than 10 weeks in duration had a most likely small effect on CMJ height performance (ES = 0.58; 95 % CI 0.25-0.91). In contrast, plyometric training durations greater than 10 weeks had a most likely large effect on CMJ height (ES = 1.87; 95 % CI 0.73-3.01). The effect of plyometric training on concentric-only squat jump (SJ) height was likely small (ES = 0.44; 95 % CI -0.09 to 0.97). Similar effects were observed on SJ height after 6 weeks of plyometric training in amateur (ES = 0.35) and young (ES = 0.49) athletes, respectively. The effect of plyometric training on CMJ height with the arm swing was likely large (ES = 1.31; 95 % CI -0.04 to 2.65). The largest plyometric training effects were observed in drop jump (DJ) height performance (ES = 3.59; 95 % CI -3.04 to 10.23). Most likely extremely large plyometric training effects on DJ height performance (ES = 7.07; 95 % CI 4.71-9.43) were observed following 12 weeks of plyometric training. In contrast, a possibly small positive training effect (ES = 0.30; 95 % CI -0.63 to 1.23) was observed following 6 weeks of plyometric training. Conclusion: Plyometric training is an effective form of training to improve VJ performance (e.g. CMJ, SJ and DJ) in female athletes. The benefits of plyometric training on VJ performance are greater for interventions of longer duration (=10 weeks).